An analysis of Norwegian public health nursing curricula: Where is the nursing literature?. Issue 1 (28th September 2021) - Laholt, Hilde; Bergvoll, Lise‐Marie; Fjelldal, Sunniva Solhaug; Clancy, Anne
Abstract: Background: Norwegian public health nurses prevent diseases and promote health in children and young people aged 0–20 and their families. Public health nursing programs prepare students for their practical role and provide relevant theoretical knowledge. Objectives: To gain knowledge of the literature in the Norwegian public health nursing curricula, and to examine further the nursing base in these curricula. Design: An explorative and descriptive design was chosen. Sample: Reading lists based on syllabus documents from the 10 higher educational institutions in Norway offering programs in public health nursing. Measurements: A summative content analysis and a categorization of content from reading lists were performed. Results: Numerical information on the content and categorization of reading lists shows that social science and humanities literature dominates, followed by psychology and medicine. Nursing texts, theories and philosophy comprise only a minor part of the curricula. Conclusion: The paper provides valuable data on the theoretical focus in Norwegian public health nursing and raises important questions about the paucity of nursing texts in the curriculum. The imbalance in reading lists in Norway should be studied further and similar studies conducted in other countries to encourage reflection on the theoretical content of public health nursing education globally.